BASICS project will adopt two commercial seed systems model_Dr Nittukar Hemant - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Dr. Nittukar Hemant explains 2 commercial models to drive cassava seed systems sustainability